Self-heating diaphragm core and preparation method thereof

By using modified starch binder and collaboratively modified chitosan porous filler, the problem of poor dispersion of iron powder and toner in the preparation of self-heating diaphragm core is solved, and efficient and stable heating and thermal conductivity are achieved.

CN119868045AInactive Publication Date: 2025-04-25ZHEJIANG ZHENSHI MINGYAN HEALTH IND CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202510054491.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-14
Publication Date
2025-04-25
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

During the preparation process of the self-heating diaphragm core, due to the difference in mass between iron powder and carbon powder, the dispersion is poor, which in turn affects the heating performance and efficiency.

Method used

The self-heating membrane core was prepared by dry mixing using active metal powder, conductive agent, modified starch binder, water-absorbing material, salt solution and porous fillers made by co-modified chitosan of 2-indene carboxylic acid and 2-(1H-indole)-4-acetic acid. The modified starch binder forms a crosslinked structure through the modification of starch and sodium carboxymethylcellulose, which improves the bonding performance and thermal stability; the porous filler enhances high temperature resistance through the π-π stacking structure.

Benefits of technology

The heating performance and efficiency of the self-heating diaphragm core is improved, the thermal conductivity is enhanced, and the dispersion problem is avoided due to mass differences is improved. At the same time, the anti-aging and thermal expansion properties of the adhesive are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005240978970000031
    Figure BDA0005240978970000031
Patent Text Reader

Abstract

The invention relates to the technical field of self-heating products, in particular to a self-heating membrane core and a preparation method thereof.The self-heating membrane core is prepared from, by mass, 50-80 parts of active metal powder, 50-80 parts of conductive agent, 8-15 parts of binder, 20-30 parts of water absorption material, 24-28 parts of salt solution and 40-60 parts of filler; the filler is a porous material which is prepared by reacting chitosan with 2-indene carboxylic acid and 2-(1H-indole)-4-acetic acid. The self-heating membrane core is good in heating performance, high in efficiency, good in heat conduction performance and environmentally friendly.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of self-heating products, and in particular to a self-heating diaphragm core and a preparation method thereof. Background Art

[0002] As a technology that uses chemical reaction or electric heating principle to generate heat, the self-heating diaphragm core has been widely used in the fields of thermal insulation materials, medical care, outdoor products, etc. The chemical exothermic self-heating body mainly uses raw materials such as iron powder, activated carbon, water, inorganic salt, etc. to release heat through oxidation reaction. For example, CN113940809A discloses "a simple thin-sheet self-heating body and its preparation method and application" with pig iron powder, activated carbon, polypropylene fiber, xanthan gum, sodium carboxymethyl cellulose and sodium polyacrylate, industrial salt, vermiculite and water as the main raw materials. The heating body will not cause the problem of leakage of heating substances, and at the same time increase the heat preservation effect of the heating body.

[0003] For example, CN106473860A discloses a "thin self-heating body and its preparation method" which is made from iron powder, activated carbon, salt, water, gum arabic or xanthan gum and molecular sieves. The heating body has a uniform and stable heating temperature and will not cause problems such as bag falling and powder leakage, and will not cause low-temperature burns.

[0004] For example, CN112704635A discloses "a self-heating body and its preparation method" which is made of iron powder, activated carbon, moxa fiber, filler, electrolyte, glue and water. The heating body can continuously generate heat to achieve the effect of "moxibustion on the body" and "moxibustion at any time".

[0005] However, during the preparation process of the self-heating diaphragm core, poor dispersion will occur due to the quality difference between iron powder and carbon powder, which in turn affects the heating performance and efficiency of the self-heating diaphragm core.

[0006] Therefore, it is urgent to develop a self-heating diaphragm core with good heating performance, high efficiency and good thermal conductivity. Summary of the invention

[0007] The main purpose of the present invention is to provide a self-heating diaphragm core and a preparation method thereof, wherein the self-heating diaphragm core has good heating performance and high efficiency, and also has good thermal conductivity.

[0008] In order to achieve the above object, the technical solution adopted by the present invention is as follows:

[0009] The present invention provides a self-heating diaphragm core, and the preparation of the self-heating diaphragm core includes the following raw materials in parts by weight: 50 to 80 parts of active metal powder, 50 to 80 parts of conductive agent, 8 to 15 parts of binder, 20 to 30 parts of water-absorbing material, 24 to 28 parts of salt solution and 40 to 60 parts of filler; the filler is a porous material prepared by the reaction of chitosan with 2-indenecarboxylic acid and 2-(1H-indole)-4-acetic acid.

[0010] In some embodiments, the particle size of the active metal powder is 100-300 meshes.

[0011] In some embodiments, the particle size of the conductive agent is 100-300 meshes.

[0012] In some embodiments, the method for preparing the binder comprises the following steps:

[0013] S1. Disperse starch in deionized water, raise the temperature to 30-40° C., adjust the pH of the system to 8-9, then add 2,3-pyridinedicarboxylic acid anhydride aqueous solution, stir at constant temperature for 2-4 hours, during which the pH of the system is controlled to be unchanged, adjust the pH to neutral after the reaction, rinse with anhydrous ethanol, and obtain pyridine-modified starch after drying;

[0014] S2, cooling thionyl chloride to -5 to 0°C, then adding the pyridine-modified starch in step S1, stirring at a constant temperature for 1 to 3 hours, filtering after the reaction, washing with ethanol, and drying to obtain acyl chloride-modified starch;

[0015] S3, mixing the acyl chloride modified starch in step S2 with N,N-dimethylformamide, adding 1,4-butanediamine and an acid binding agent, heating to 50-60° C. and stirring at a constant temperature for 12-18 hours, washing with deionized water after the reaction, concentrating and drying under reduced pressure to obtain a composite modified starch;

[0016] S4, mix sodium carboxymethyl cellulose with deionized water, heat to 30-40°C and stir for 12-16 hours, then add NaIO 4 Solution, diluted H 2 SO 4 The pH value was adjusted to 2-3, and the mixture was stirred at a constant temperature for 4-6 hours in a light-proof condition. After the reaction, ethanol was added for precipitation, and the mixture was filtered, washed, and freeze-dried to obtain sodium aldehyde carboxymethyl cellulose;

[0017] S5. Add the composite modified starch, modified aminopropyl POSS in step S3 and the aldehyde carboxymethyl cellulose sodium in step S4 into deionized water for mixing and dispersion, heat to 35-45° C., adjust the system pH to 4-5, stir at a constant temperature for 12-16 hours, and after the reaction is completed, freeze-dry to obtain a binder.

[0018] The adhesive of the present application has good adhesive properties, thermal expansion resistance and aging resistance. The reason may be that the adhesive uses starch and sodium carboxymethyl cellulose as main raw materials, and the starch and carboxymethyl cellulose are modified and then combined by Schiff base to form a cross-linked structure. On the one hand, the side-chain structure of the adhesive has phenyl, pyridine, hydroxyl and carboxyl groups, among which pyridine, hydroxyl and carboxyl groups can form coordination bonds with active metals to anchor the metals on the adhesive, and phenyl can form a π-π stacking effect with carbon powder to anchor it on the adhesive, so that the active metal and carbon powder are closely attached together, avoiding the problem of uneven dispersion of active metal and carbon powder due to quality difference; on the other hand, the adhesive of the present application has a cross-linked structure, which improves the viscosity of the adhesive, and the structure is stable and can resist thermal expansion; on the third hand, the adhesive structure contains a large amount of hindered phenol structure, which can improve the aging resistance of the adhesive; on the fourth hand, the main raw materials of the adhesive of the present application are starch and sodium carboxymethyl cellulose, so that the prepared adhesive has good biodegradability, is environmentally friendly, and has no secondary pollution.

[0019] In some embodiments, the structure of the modified aminopropyl POSS is as shown in Formula I

[0020]

[0021] In some embodiments, the preparation method of the modified aminopropyl POSS comprises the following steps:

[0022] A1. Mix sodium hydroxide solution and acetone, cool to -20 to -10°C, add 3-aminopropyltrimethoxy, stir at constant temperature for 20 to 30 minutes, then raise the temperature to reflux, stir for 22 to 26 hours, adjust the pH of the system to neutral after the reaction, filter, concentrate and dry under reduced pressure to obtain aminopropyl POSS;

[0023] A2, the aminopropyl POSS in step A1 is mixed with 2,6-di-tert-butyl-4-chlorophenol and 1-chloronaphthalene, and added into N,N-dimethylformamide, an acid binding agent is added, the temperature is raised to 35-45° C. and stirred at a constant temperature for 12-14 h, and after the reaction is completed, the modified aminopropyl POSS is filtered to obtain.

[0024] In some embodiments, in step S1, the mass of the 2,3-pyridinedicarboxylic acid anhydride is 3-4 wt % of the starch.

[0025] In some embodiments, the acid binding agent is any one of sodium carbonate, potassium carbonate, sodium bicarbonate and potassium bicarbonate.

[0026] In some embodiments, in step S2, the mass ratio of thionyl chloride to pyridine-modified starch is 1:(0.1-0.3).

[0027] In some embodiments, in step S3, the volume mass ratio of the N,N-dimethylformamide to the acyl chloride modified starch is 8 to 15 mL / g.

[0028] In some embodiments, in step S3, the molar ratio of the acid binding agent to 1,4-butanediamine is (1.2-1.5):1.

[0029] In some embodiments, the molar ratio of the 1,4-butanediamine to the 2,3-pyridinedicarboxylic anhydride is (0.8-1):1.

[0030] In some embodiments, in step S5, the mass ratio of the composite modified starch, modified aminopropyl POSS and aldehyde carboxymethyl cellulose sodium is (0.1-0.3):(0.05-0.15):1.

[0031] In some embodiments, the starch is selected from amylose, and the number average molecular weight is 4×10 5 ~9×10 5 g / mol.

[0032] In some embodiments, in step A2, the molar ratio of aminopropyl POSS, 2,6-di-tert-butyl-4-chlorophenol and 1-chloronaphthalene is 1:(0.8-1):(6-6.2).

[0033] In some embodiments, the water absorbing material is one or more of hydrogel, cellulose, activated carbon, silica gel, sponge and clay.

[0034] In some embodiments, the method for preparing the filler comprises the following steps:

[0035] A1, mixing chitosan with acetic acid solution to prepare a chitosan solution;

[0036] A2, mixing 2-indenecarboxylic acid, 2-(1H-indole)-4-acetic acid and carbodiimide hydrochloride, adding ethanol solution to prepare a mixed liquid;

[0037] A3. Add the mixed liquid in step A2 to the chitosan solution in step A1, stir at room temperature for 12 hours, and use acetic acid to maintain the pH of the system at 5-6. After the reaction is completed, dialyze and freeze-dry to obtain the filler.

[0038] The porous material made of chitosan used by the applicant can increase the heating temperature and duration of the self-heating diaphragm core and improve the heating efficiency. The reason may be that the porous material has a porous structure that can enable the self-heating diaphragm core to contact more air and improve the heating efficiency. However, the applicant found in the research that the porous material made of chitosan is very easy to be damaged during the pressing process of the self-heating diaphragm core, resulting in a decrease in heating efficiency instead of an increase.

[0039] The filler prepared by the synergistic modification of chitosan by using 2-indenecarboxylic acid and 2-(1H-indole)-4-acetic acid can not only improve the heating efficiency of the self-heating diaphragm core, but also prevent damage due to excessive temperature during the pressing process. The reason may be that the filler structure contains a large number of phenyl structures. When the fillers are mixed, a π-π stacking structure can be formed to enhance the high temperature resistance of the filler, thereby making it not easily damaged during high-temperature hot pressing.

[0040] In some embodiments, the mass ratio of 2-indenecarboxylic acid, 2-(1H-indole)-4-acetic acid and chitosan is 1:(1-1.3):(1.2-1.6).

[0041] Another aspect of the present invention provides a method for preparing a self-heating diaphragm core, comprising the following steps:

[0042] B1. Mixing active metal powder, conductive agent, binder, water-absorbing material, salt solution and filler to obtain mixed powder;

[0043] B2, conveying the mixed powder obtained in step B1 to a pressing device for pressing and forming a base film;

[0044] B3. Cut the base film formed in step B2 according to size requirements to obtain a self-heating film core.

[0045] In some embodiments, the mixing method in step S1 is specifically:

[0046] B11, premixing stage: speed is 600-1000 rpm, time is 100-500 sec;

[0047] B12, rapid mixing stage: rotation speed is 1600-2400 rpm, time is 100-1000 sec;

[0048] B13, slow mixing stage: speed is 600-1000 rpm, time is 100-500 sec;

[0049] B14, slow mixing and discharging stage: the rotation speed is 300-700 rpm.

[0050] In some embodiments, in step B2, the pressing temperature is 40-300°C.

[0051] Compared with the prior art, the present invention has the following beneficial effects:

[0052] (1) The self-heating diaphragm core of the present invention is prepared by dry mixing active metal powder, conductive agent, adhesive, water-absorbing material, salt solution and filler. The self-heating diaphragm core has good heating performance and high efficiency, and also has good thermal conductivity.

[0053] (2) The binder of the present invention uses environmentally friendly and biodegradable natural extract starch and sodium carboxymethyl cellulose as starting materials. The starch and sodium carboxymethyl cellulose are modified separately so that the two can form a Schiff base and then form a cross-linked structure. The binder has phenyl, pyridine, hydroxyl and carboxyl groups on the side chains. The pyridine, hydroxyl and carboxyl groups can form coordination bonds with the active metal to anchor the metal on the binder, while the phenyl groups can form a π-π stacking effect with the carbon powder to anchor it on the binder, so that the active metal and the carbon powder are tightly attached together, avoiding the problem of uneven dispersion of the active metal and the carbon powder due to quality differences. In addition, the binder also has good anti-aging and anti-thermal expansion properties.

[0054] (3) The filler of the present invention is prepared by using 2-indenecarboxylic acid and 2-(1H-indole)-4-acetic acid to synergistically modify chitosan, and its structure contains a large number of phenyl structures. When the fillers are mixed, a π-π stacking structure can be formed to enhance the high temperature resistance of the filler, thereby making it less likely to be damaged during high temperature hot pressing. DETAILED DESCRIPTION

[0055] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0056] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0057] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as commonly understood by those skilled in the art. Although only preferred methods and materials are described herein, any methods and materials similar or equivalent to those described herein may also be used in the practice or testing of the present invention. Various modifications and variations may be made to the specific embodiments of the present invention specification without departing from the scope or spirit of the present invention, which will be apparent to those skilled in the art. Other embodiments obtained from the present invention specification will be apparent to the technician. The present application specification and examples are exemplary only.

[0058] It should be noted that the operations of "drying", "filtering" and "stirring" described in the present invention are routine operations of those skilled in the art and can be selected according to actual operations.

[0059] In the following preparation examples, the number average molecular weight of amylose is 6×10 5 g / mol; CAS number of sodium carboxymethyl cellulose is 9004-32-4.

[0060] Preparation Example 1

[0061] The preparation method of modified aminopropyl POSS comprises the following steps:

[0062] A1, 10mL 2wt% sodium hydroxide solution was mixed with 100mL acetone, cooled to -15°C, 0.1mol 3-aminopropyl trimethoxy was added thereto, and the mixture was stirred at a constant temperature for 25min, then the temperature was raised to reflux, and stirred for 24h. After the reaction was completed, 1mol / L dilute hydrochloric acid was added to adjust the pH of the system to 6.5, and the mixture was filtered, concentrated under reduced pressure and dried to obtain aminopropyl POSS;

[0063] A2. Mix 0.1 mol of the aminopropyl POSS in step A1 with 0.009 mol of 2,6-di-tert-butyl-4-chlorophenol and 0.61 mol of 1-chloronaphthalene, add into 1 L of N,N-dimethylformamide, add 1 mol of sodium bicarbonate, raise the temperature to 40° C. and stir for 13 h. After the reaction is completed, filter to obtain modified aminopropyl POSS.

[0064] Preparation Example 2

[0065] The preparation method of the binder comprises the following steps:

[0066] S1. 10 g of amylose was dispersed in 50 mL of deionized water, the temperature was raised to 35° C., the pH of the system was adjusted to 8.5 with a 1 wt % sodium hydroxide solution, and then 20 mL of an aqueous solution containing 3.5 g of 2,3-pyridinedicarboxylic acid anhydride was added thereto, and the mixture was stirred at a constant temperature for 3 h. During this period, the pH of the system was controlled to be unchanged. After the reaction was completed, the pH was adjusted to 7 with 1 mol / L dilute hydrochloric acid, and the mixture was rinsed with anhydrous ethanol and dried to obtain pyridine-modified starch;

[0067] S2, cooling 60g of thionyl chloride to -3°C, then adding the pyridine-modified starch obtained in step S1, stirring at a constant temperature for 2h, filtering after the reaction, washing with ethanol, and drying to obtain acyl chloride-modified starch;

[0068] S3, mixing the acyl chloride modified starch obtained in step S2 with 132 mL of N,N-dimethylformamide, adding 1.86 g of 1,4-butanediamine and 2.56 g of sodium bicarbonate, heating to 55° C. and stirring at a constant temperature for 16 h, washing with deionized water after the reaction, concentrating and drying under reduced pressure to obtain a composite modified starch;

[0069] S4, mix 70g sodium carboxymethyl cellulose with 1L deionized water, heat to 35℃ and stir for 14h, then add 700mL 0.11g / mL NaIO 4 Solution, with 1mol / LH 2 SO 4 The pH value was adjusted to 2.5, and the mixture was stirred at a constant temperature for 5 h in a light-proof condition. After the reaction was completed, ethanol was added for precipitation, and the mixture was filtered, washed, and freeze-dried to obtain sodium aldehyde carboxymethyl cellulose;

[0070] S5. Add 13 g of the composite modified starch in step S3, 6.5 g of modified aminopropyl POSS and 65 g of the aldehyde carboxymethyl cellulose sodium in step S4 into 1.5 L of deionized water for mixing and dispersion, heat to 40°C, adjust the system pH to 4.5, stir at a constant temperature for 14 h, and after the reaction is completed, freeze-dry to obtain a binder.

[0071] Wherein, the modified aminopropyl POSS is prepared by Preparation Example 1.

[0072] Preparation Example 3

[0073] The preparation method of the filler comprises the following steps:

[0074] A1. Mix 3 g of chitosan with 100 mL of 0.3 mol / L acetic acid solution to prepare a chitosan solution;

[0075] A2, 2.4 g of 2-indenecarboxylic acid, 2.4 g of 2-(1H-indole)-4-acetic acid and 6.8 g of carbodiimide hydrochloride were mixed, and 200 mL of 55 wt% ethanol solution was added to prepare a mixed liquid;

[0076] A3. Add the mixed liquid in step A2 to the chitosan solution in step A1, stir at room temperature for 12 hours, and use acetic acid to maintain the pH of the system at 5.5. After the reaction is completed, dialyze and freeze-dry to obtain the filler.

[0077] Preparation Example 4

[0078] The preparation method of the filler and the specific implementation method are the same as those in Preparation Example 3, except that no 2-(1H-indole)-4-acetic acid is added.

[0079] Example 1

[0080] A self-heating membrane core, the preparation of which includes the following raw materials by weight: 65 parts of 200-mesh iron powder, 65 parts of 200-mesh carbon powder, 12 parts of binder, 25 parts of clay, 26 parts of 18wt% sodium chloride solution and 50 parts of filler; the filler is a porous material prepared by the reaction of chitosan with 2-indenecarboxylic acid and 2-(1H-indole)-4-acetic acid.

[0081] Among them, the binder is prepared by Preparation Example 2, and the filler is prepared by Preparation Example 3.

[0082] The method for preparing a self-heating diaphragm core comprises the following steps:

[0083] B1, mixing iron powder, carbon powder, binder, clay, sodium chloride solution and filler at a rotation speed of 800 rpm for 300 seconds, at 2000 rpm for 550 seconds, at 800 rpm for 300 seconds, and then discharging at a rotation speed of 500 rpm to obtain a mixed powder;

[0084] B2, conveying the mixed powder obtained in step B1 to a pressing device for pressing at 200° C. to form a base film;

[0085] B3. Cut the base film formed in step S2 according to size requirements to obtain a self-heating film core.

[0086] Example 2

[0087] A self-heating diaphragm core, the preparation of which includes the following raw materials by weight: 50 parts of 100-mesh iron powder, 50 parts of 100-mesh carbon powder, 8 parts of binder, 20 parts of clay, 24 parts of 18wt% sodium chloride solution and 40 parts of filler; the filler is a porous material prepared by the reaction of chitosan with 2-indenecarboxylic acid and 2-(1H-indole)-4-acetic acid.

[0088] Among them, the binder is prepared by Preparation Example 2, and the filler is prepared by Preparation Example 3.

[0089] The method for preparing a self-heating diaphragm core comprises the following steps:

[0090] B1: iron powder, carbon powder, binder, clay, sodium chloride solution and filler were mixed at a rotation speed of 600 rpm for 500 seconds, at 1600 rpm for 1000 seconds, at 600 rpm for 500 seconds, and then discharged at a rotation speed of 300 rpm to obtain a mixed powder;

[0091] B2: The mixed powder obtained in step B1 is conveyed to a pressing device for pressing at 40° C. to form a base film;

[0092] B3: Cut the base film formed in step B2 according to size requirements to obtain a self-heating film core.

[0093] Example 3

[0094] A self-heating membrane core, the preparation of which includes the following raw materials by weight: 80 parts of 300-mesh iron powder, 80 parts of 300-mesh carbon powder, 15 parts of binder, 30 parts of clay, 28 parts of 18wt% sodium chloride solution and 60 parts of filler; the filler is a porous material prepared by reacting chitosan with 2-indenecarboxylic acid and 2-(1H-indole)-4-acetic acid.

[0095] Among them, the binder is prepared by Preparation Example 2, and the filler is prepared by Preparation Example 3.

[0096] The method for preparing a self-heating diaphragm core comprises the following steps:

[0097] B1: iron powder, carbon powder, binder, clay, sodium chloride solution and filler were mixed at a rotation speed of 1000 rpm for 100 seconds, at 2400 rpm for 100 seconds, at 1000 rpm for 100 seconds, and then discharged at a rotation speed of 700 rpm to obtain a mixed powder;

[0098] B2: conveying the mixed powder obtained in step B1 to a pressing device for pressing at 300° C. to form a base film;

[0099] B3: Cut the base film formed in step B2 according to size requirements to obtain a self-heating film core.

[0100] Example 4

[0101] A self-heating diaphragm core and a preparation method thereof, wherein the specific implementation manner is the same as that of Example 1, except that the filler is prepared by Preparation Example 4.

[0102] Example 5

[0103] A self-heating diaphragm core and a preparation method thereof, the specific implementation manner is the same as that of Example 1, except that the iron powder is 70 mesh.

[0104] Example 6

[0105] A self-heating diaphragm core and a preparation method thereof, the specific implementation manner is the same as that of Example 1, except that the carbon powder is 70 mesh.

[0106] Example 7

[0107] A self-heating diaphragm core and a preparation method thereof, the specific implementation manner is the same as that of Example 1, except that the preparation method of the self-heating diaphragm core comprises the following steps:

[0108] B1, mixing iron powder, carbon powder, binder, clay, sodium chloride solution and filler at a rotation speed of 1400 rpm for 300 seconds, at 2000 rpm for 550 seconds, at 800 rpm for 300 seconds, and then discharging at a rotation speed of 500 rpm to obtain a mixed powder;

[0109] B2, conveying the mixed powder obtained in step B1 to a pressing device for pressing at 200° C. to form a base film;

[0110] B3. Cut the base film formed in step B2 according to size requirements to obtain a self-heating film core.

[0111] Comparative Example 1

[0112] A self-heating diaphragm core and a preparation method thereof, wherein the specific implementation manner is the same as that of Example 1, except that an equal mass portion of xanthan gum is used instead of a binder.

[0113] Comparative Example 2

[0114] A self-heating diaphragm core and a preparation method thereof, the specific implementation manner is the same as that of Example 1, except that an equal mass portion of vermiculite is used instead of filler.

[0115] Performance Testing:

[0116] (1) Heating performance: The self-heating diaphragm core is placed in a tabletting mold with inner packaging materials on the top and bottom, and pressed into a square to obtain a self-heating body. The center of the self-heating body is placed directly above the temperature probe of a paperless temperature recorder. A double layer of towel is covered on the top of the heating sheet for insulation. The room temperature, i.e., the starting temperature, is about 25°C. The maximum heating temperature and heating duration (the duration of the temperature exceeding 40°C) are tested.

[0117] The self-heating diaphragm cores of the embodiments and comparative examples were tested according to the above method. The test results are shown in Table 1.

[0118] Table 1

[0119] Fever temperature / ℃ Duration / min Example 1 60.3 123 Example 2 58.7 126 Example 3 61.1 122 Example 4 54.9 118 Example 5 56.2 116 Example 6 55.4 119 Example 7 56.1 112 Comparative Example 1 39.4 48 Comparative Example 2 40.3 41

[0120] According to the data in Table 1, the self-heating diaphragm cores prepared in Examples 1 to 3 have good heating performance; in Example 4, 2-(1H-indole)-4-acetic acid was not added during the preparation of the filler, resulting in a decrease in the heating performance of the self-heating diaphragm core; in Example 5, the heating performance of the self-heating body was decreased due to the change in the mesh size of the iron powder; in Example 6, the heating performance of the self-heating body was decreased due to the change in the mesh size of the carbon powder; in Example 7, the heating performance of the self-heating diaphragm core was decreased due to the change in the mixing speed in the premixing stage; in Comparative Example 1, since the same mass parts of xanthan gum were used instead of the binder, the dispersibility of the iron powder and the carbon powder became worse, resulting in a decrease in the heating performance of the self-heating diaphragm core; in Comparative Example 2, since the same mass parts of vermiculite were used instead of the filler, the dispersibility of the iron powder, carbon powder and vermiculite became worse, resulting in a decrease in the heating performance of the self-heating diaphragm core.

[0121] Finally, it should be noted that the above specific implementation methods are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to examples, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present invention, which should be included in the scope of the claims of the present invention.

Claims

1. A self-heating diaphragm core, characterized in that: The preparation of the self-heating film core includes the following raw materials in parts by weight: 50 to 80 parts of active metal powder, 50 to 80 parts of conductive agent, 8 to 15 parts of binder, 20 to 30 parts of water-absorbing material, 24 to 28 parts of salt solution and 40 to 60 parts of filler; the filler is a porous material prepared by the reaction of chitosan with 2-indenecarboxylic acid and 2-(1H-indole)-4-acetic acid.

2. The self-heating diaphragm core according to claim 1, characterized in that: The particle size of the active metal powder is 100-300 meshes.

3. The self-heating diaphragm core according to claim 1, characterized in that: The particle size of the conductive agent is 100-300 meshes.

4. The self-heating diaphragm core according to claim 1, characterized in that: The preparation method of the binder comprises the following steps: S1. Disperse starch in deionized water, raise the temperature to 30-40° C., adjust the pH of the system to 8-9, then add 2,3-pyridinedicarboxylic acid anhydride aqueous solution, stir at constant temperature for 2-4 hours, during which the pH of the system is controlled to be unchanged, adjust the pH to neutral after the reaction, rinse with anhydrous ethanol, and obtain pyridine-modified starch after drying; S2, cooling thionyl chloride to -5 to 0°C, then adding the pyridine-modified starch in step S1, stirring at a constant temperature for 1 to 3 hours, filtering after the reaction, washing with ethanol, and drying to obtain acyl chloride-modified starch; S3, mixing the acyl chloride modified starch in step S2 with N,N-dimethylformamide, adding 1,4-butanediamine and an acid binding agent, heating to 50-60° C. and stirring at a constant temperature for 12-18 hours, washing with deionized water after the reaction, concentrating and drying under reduced pressure to obtain a composite modified starch; S4, mixing sodium carboxymethyl cellulose with deionized water, heating to 30-40°C and stirring at constant temperature for 12-16 hours, then adding NaIO4 solution thereto, adjusting the pH to 2-3 with dilute H2SO4, stirring at constant temperature for 4-6 hours under light-proof conditions, adding ethanol precipitation after the reaction, filtering, washing, and freeze-drying to obtain sodium aldehyde carboxymethyl cellulose; S5. Add the composite modified starch, modified aminopropyl POSS in step S3 and the aldehyde carboxymethyl cellulose sodium in step S4 into deionized water for mixing and dispersion, heat to 35-45° C., adjust the system pH to 4-5, stir at a constant temperature for 12-16 hours, and after the reaction is completed, freeze-dry to obtain a binder.

5. The self-heating diaphragm core according to claim 1, characterized in that: The water absorbing material is one or more of hydrogel, cellulose, activated carbon, silica gel, sponge and clay.

6. The self-heating diaphragm core according to claim 1, characterized in that: The preparation method of the filler comprises the following steps: A1, mixing chitosan with acetic acid solution to prepare a chitosan solution; A2, mixing 2-indenecarboxylic acid, 2-(1H-indole)-4-acetic acid and carbodiimide hydrochloride, adding ethanol solution to prepare a mixed liquid; A3. Add the mixed liquid in step A2 to the chitosan solution in step A1, stir at room temperature for 12 hours, and use acetic acid to maintain the pH of the system at 5-6. After the reaction is completed, dialyze and freeze-dry to obtain the filler.

7. The self-heating diaphragm core according to claim 6, characterized in that: The mass ratio of the 2-indenecarboxylic acid, 2-(1H-indole)-4-acetic acid and chitosan is (0.7-1):(0.7-1):

1.

8. A method for preparing a self-heating diaphragm core according to any one of claims 1 to 7, characterized in that: The steps include: B1. Mixing active metal powder, conductive agent, binder, water-absorbing material, salt solution and filler to obtain mixed powder; B2, conveying the mixed powder obtained in step B1 to a pressing device for pressing and forming a base film; B3. Cut the base film formed in step B2 according to size requirements to obtain a self-heating film core.

9. The method for preparing the self-heating diaphragm core according to claim 8, characterized in that: The mixing method in step S1 is specifically as follows: B11, premixing stage: speed is 600-1000 rpm, time is 100-500 sec; B12, rapid mixing stage: rotation speed is 1600-2400 rpm, time is 100-1000 sec; B13, slow mixing stage: speed is 600-1000 rpm, time is 100-500 sec; B14, slow mixing and discharging stage: the rotation speed is 300-700 rpm.

10. The method for preparing the self-heating diaphragm core according to claim 8, characterized in that: In the step B2, the pressing temperature is 40-300°C.

Citation Information

Patent Citations

  • Thin self-heating body and preparation method thereof

    CN106473860A

  • Self-heating element and preparation method therefor

    CN112704635A

  • Simple lamellar type self-heating element and preparation method and application thereof

    CN113940809A

  • Method for preparing functional heating patch

    CN106632900A

  • Eye nursing heating sheet and preparation method

    CN107997871A